THE IMPORTANCE OF FAMILY PSYCHOLOGY IN SOLVING ECONOMIC PROBLEMS IN THE FAMILY - Khaitova Fotima Tillavoldiyevna, (PEDAGOGS, 2025)
Abstract: It is not enough to quickly inform about the events happening in the life of the society today, people in the modern world are increasingly facing the problem of family economy. In recent years, the economic problems that have arisen in the household, along with the negative impact on interpersonal relations in the family, have also led to a decrease in the level of education of children. Some people get through them easily, but for some couples it ends in divorce.